ANALISIS MAJAS DALAM NOVEL PULANG KARYA TERE LIYE - Rizky Amelia Fatmi Dewi; Antonius Totok Priyadi; Agus Wartiningsi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
AbstractThe study was supported by the interest researchers lifted by the majas found in the Pulangnovels of tere liye. From Pulang novels we can find our way home through battle after battle, toembrace all the hatred and pain. “Pulang” is a word that can mean returning to the same placeafter getting tired, getting some rest, getting some soul-crushing afterthought. As for theproblem of researchers, this is how advanced comparisons, contradictions, affirmations,allusions and implementation applications majas in the Pulang novels of Tere Liye. Thepurpose of this study is to describe majas comparisons, contradictions, assertions, insinuationsand implementation plans based on majas analysis in the Pulang novels of Tere Liye at highschool. The study uses qualitative descriptive methods. The object in this study is Tere Liye'sPulang novel. The source of the data in this study is Tere Liye's Pulang novel. The data used inthis study is the comparative majas, veracity, affirmation, and innuendo found in the homenovels of Tere Liye. The techniques for collecting data in this study are done with documentarystudies. The research instruments used are with data recorders tables. The data analysistechniques used are exposure and context analysis techniques. The data-validity testingtechnique used was surveillance persistence, triangulation and sufficient reference. Based onthe findings of the study, there are three stages. By comparison, the personification of 10examples, hyperbole 10 examples, Parable/simile 13 examples, and metaphor 1 example,metaphor of opposition, namely Hyperlone prosteron 2 example, majas affirmation, which is theclimax of 3 sample results. The study is implemented in high school learning activities at the XIIsemester to complete curriculum 2013.Keywords: Analysis, Major, Novel